Pendampingan Program Cetak Sawah Berbasis Foto Udara di Kecamatan Sungai Lais, Kabupaten Musi Banyuasin - Yogie Ardiwinata; Arie Anggara; Annisa Kurnia Shalihat (Komatika: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to support the Cetak Sawah Program in Sungai Lais District, Musi Banyuasin Regency, South Sumatra through the use of unmanned aerial vehicle (UAV) or drone-based aerial photography technology. This program is an implementation of the Tridharma of Higher Education in the aspect of community service by integrating geospatial science and empowering local farmers. The main problem in this area is the limited accurate spatial data for new land planning and the lack of community capacity in utilizing modern mapping technology. The activity was carried out through mapping potential “cetak sawah” areas using orthophotos obtained from aerial acquisition and assistance from the community and village government in the verification and land planning process. The results of the activity showed that the use of aerial photography was able to increase the accuracy of potential land identification by up to 90% compared to manual methods, as well as speed up the field validation process. In addition, the community gained increased knowledge and basic skills in digital mapping technology. This activity strengthens collaboration between universities, local governments, and the community as a tangible manifestation of academic contributions to food security and sustainable agricultural development at the local level.